The Effect of Heart Rate Variability Biofeedback Training on Vagal Tone in Athletically Talented Secondary School Students - Andrea M. Firth; Torvald F. Ask; Stefan Sütterlin; Ricardo G. Lugo (MDPI AG, 2022)
This study examines whether twelve sessions of heart rate variability biofeedback training would improve vagally mediated heart rate variability. If so, it would go some way in explaining why breathing-based interventions reduce clinical symptoms and improve non-clinical performance outcomes. Methods: Thirty participants (N = 30, Nfemale = 13) aged 14-13-year-old, all talented athletes, from a sport specialist school in SE London UK, were randomly divided into three groups, a control group, a psychology skills training combined with heart rate variability biofeedback training group, and a heart rate variability biofeedback only group. For the combined group, a variety of typical psychological skill training techniques were also used. Results: Paired participant t-test and the Wilcoxon Signed Rank test found non-significant differences between pre- and post-intervention measurements of heart rate variability. Non-significant results remained even after pooling the biofeedback training groups (n = 19). Conclusions: Our results do not indicate that beneficial effects associated with focused breathing training can be attributed to improved vagal tone. Further investigation into the underlying mechanisms of the benefits of focused breathing techniques is necessary to maximize clinical and non-clinical outcomes.